2022
DOI: 10.1002/pros.24340
|View full text |Cite
|
Sign up to set email alerts
|

Germline genetics of prostate cancer

Abstract: Background: An important fraction (>/~10%) of men with high-risk, localized prostate cancer and metastatic prostate cancer carry germline (heritable) pathogenic and likely pathogenic variants (also known as mutations) in DNA repair genes. These can represent known or suspected autosomal dominant cancer predisposition syndromes. Growing evidence suggests that pathogenic variants in key genes involved in homologous recombination and mismatch DNA repair are important in prostate cancer initiation and/or the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…A meta-analysis including 19 studies revealed that carriers of P/LPVs in ATM have a cumulative lifetime risk of BC of 33% by age 80 years [ 13 ]. Additionally, ATM P/LPVs are also associated with a slight increased risk of OC [ 14 , 15 , 16 ], pancreatic [ 17 ] and prostate [ 18 ] cancer. The cumulative lifetime risk of BC in CHEK2 P/LPVs carriers has been estimated as 28% to 37% [ 19 , 20 ].…”
Section: Hereditary Breast and Ovarian Cancer Syndromes And Parp Inhi...mentioning
confidence: 99%
“…A meta-analysis including 19 studies revealed that carriers of P/LPVs in ATM have a cumulative lifetime risk of BC of 33% by age 80 years [ 13 ]. Additionally, ATM P/LPVs are also associated with a slight increased risk of OC [ 14 , 15 , 16 ], pancreatic [ 17 ] and prostate [ 18 ] cancer. The cumulative lifetime risk of BC in CHEK2 P/LPVs carriers has been estimated as 28% to 37% [ 19 , 20 ].…”
Section: Hereditary Breast and Ovarian Cancer Syndromes And Parp Inhi...mentioning
confidence: 99%
“…The optimal delivery model of PCa genetics care remains unclear. 7,17 Historically, germline testing has been conducted after pretest counseling by GCs. Recently, novel approaches involving oncology staff, with or without GC involvement, that is, hybrid or mainstream models, respectively, have been advocated to increase accessibility and speed.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include one study that found that men with brothers with prostate cancer were significantly more likely to develop any-risk prostate cancer, and another finding that up to 57% of prostate cancer can be attributed to genetic risk factors. 7 In fact, at least 260 germline genetic variants associated with PCa have been identified via whole-genome sequencing — a number that continues to grow as more genetic analyses on more diverse populations are conducted. 8 Germline DNA repair mutations are particularly associated with aggressive disease, metastatic progression, and cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Germline DNA repair mutations are particularly associated with aggressive disease, metastatic progression, and cancer-specific mortality. 7 , 9 Studies have shown that the percentage of mCRPC patients with germline mutations in these genes range from 8% to 16%. 9–11 …”
Section: Introductionmentioning
confidence: 99%